"Menaced Rationality": Husserl and Merleau-Ponty on the Crisis and Promise of Science. Issue 3 (December 2015) - Singer, Jonathan D.
Abstract: In this paper I provide an overview of Husserl's and Merleau-Ponty's phenomenological critique of science, and suggest that such a critique is not only necessary in order to resolve an aporia that is otherwise apparently endemic to science, but that such a critique may also offer resources for productively addressing related philosophical difficulties, particularly the relationship between ideality and materiality/"nature." Following Husserl and Merleau-Ponty, I maintain that only a phenomenologically grounded science can be consistently "scientific."